Comparison of Implicit and Explicit Solvation Models for Iota-Cyclodextrin Conformation Analysis from Replica Exchange Molecular Dynamics - Khuntawee W. (2017)
© 2017 American Chemical Society. Large ring cyclodextrins have become increasingly important for drug delivery applications. In this work, we have performed replica-exchange molecular dynamics simulations using both implicit and explicit water solvation models to study the conformational diversity of iota-cyclodextrin containing 14 α-1,4 glycosidic linked d-glucopyranose units (CD14). The new quantifiable calculation methods are proposed to analyze the openness, bending, and twisted conformation of CD14 in terms of circularity, biplanar angle, and one-directional conformation (ODC). CD14 in GB implicit water model (Igb5) was found mostly in an opened conformation with average circularity of 0.39 ± 0.16 and a slight bend with average biplanar angle of 145.5 ± 16.0°. In contrast, CD14 in TIP3P explicit water solvation is significantly twisted with average circularity of 0.16 ± 0.10, while 29.1% are ODCs. In addition, classification of CD14 conformations using a Gaussian mixture model (GMM) shows that 85.0% of all CD14 in implicit water at 300 K correspond to the elliptical conformation, in contrast to 82.3% in twisted form in explicit water. GMM clustering also reveals minority conformations of CD14 such as the 8-shape, boat-form, and twisted conformations. This work provides fundamental insights into CD14 conformation, influence of solvation models, and also proposes new quantifiable analysis techniques for molecular conformation studies in the future.